2022
DOI: 10.1590/1519-6984.241819
|View full text |Cite
|
Sign up to set email alerts
|

Helminth fauna of Norops fuscoauratus (D’Orbigny, 1837) (Squamata: Dactyloidae) in the Atlantic Forest, northeastern Brazil

Abstract: The composition of macro endoparasites associated with the lizard Norops fuscoauratus (Squamata) was analysed in two localities in the Atlantic Forest on the northeast of Brazil between December 2012 and July 2015. 74 specimens of N. fuscoauratus were examined and five species of helminths were reported, being: (a) for the population of Pernambuco: Cystacanth (Prevalence=37.5%), Physaloptera retusa Rudolphi, 1819 (Prevalence=4.16%), larva of flatworm (Prevalence=2.08%), Rhabdias sp. (Prevalence=2.08%) and Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several studies on species of the family Tropiduridae performed in different areas of the Neotropical region, have demonstrated the influence of host sex on endoparasite infection rates (Fontes et al, 2003;Pereira et al, 2012;Galdino et al, 2014;Araújo-Filho et al, 2016). In studies carried out with lizards of the families Leiosauridae (Sousa et al, 2007), Gymnophtalmidae (Oliveira et al, 2017) and Dactyloidae (Campos et al, 2021), differences in infection rates were also observed between male and female hosts.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies on species of the family Tropiduridae performed in different areas of the Neotropical region, have demonstrated the influence of host sex on endoparasite infection rates (Fontes et al, 2003;Pereira et al, 2012;Galdino et al, 2014;Araújo-Filho et al, 2016). In studies carried out with lizards of the families Leiosauridae (Sousa et al, 2007), Gymnophtalmidae (Oliveira et al, 2017) and Dactyloidae (Campos et al, 2021), differences in infection rates were also observed between male and female hosts.…”
Section: Discussionmentioning
confidence: 95%